Clinical pharmacy in medical practice: the impact of detection, prevention and resolution of Drug Therapy Problems (DTPs) on patients with chronic diseases - Kawa A. Obeid; Chiya Muhamad Ahmad (College of Pharmacy / Mustansiriyah University, 2020)
(i). Background & objective: Recently, the role of pharmacists in the healthcare settings has dramatically evolved through the application of pharmaceutical care process. However, this new role has not been fully elucidated and reflected in the Iraqi healthcare system.  Therefore, the aim of this study was to evaluate the   impact of clinical pharmacist intervention on the management of patients with common chronic diseases.  (ii) Methods: a randomised controlled trial study was performed with 125 patients with one or more of these conditions: hypertension, hyperlipidaemia and Diabetes mellitus. They have divided into two groups i.e. intervention and non-intervention groups.  (iii) Results: The results revealed that pharmacist intervention played a significantly role in the management of chronic diseases given that a significant reduction in the various clinical parameters such as blood pressure, lipid profile, HbA1c and FPG were observed among the intervention group. Apart from development of a therapeutic relationship with the patients, these results are largely amounted to the detection, prevention and resolution of a massive number of DTPs among the patients in the intervention group. (iv) interpretation & Conclusion: Clinical pharmacist intervention can play a pivotal role in the management of patients with chronic diseases. This could be extended to the other healthcare settings as well. Moreover, clinical pharmacist plays a key role in the achievement of therapeutical goals and avoiding Drug Therapy Problems (DTPs).